Comparison of Assessment of Abbreviated Burn Severity Index (Absi) and Belgian Outcome of Burn Injury (BOBI) at H. Adam Malik General Hospital - Rifwanul Basir Nasution; Utama Abdi Tarigan; Frank Bietra Buchari (Talenta Publisher, 2022)
Background: Assessment of length of stay and mortality in patients with burn injuries is essential to support clinicians in making clinical decisions. In Indonesia, there are several scoring systems used by hospital centers to assess the mortality of burn patients, such as the Belgian Outcome of Burn Injury (BOBI) and the Abbreviated Burn Severity Index (ABSI). However, different results were obtained in studies that examined the comparison of the results of the scoring system. Method: The type of research used in this research is unpaired comparative analysis research using a cross-sectional design. The data to be used is secondary data taken from medical records. Results: Respondents with death status were found in the serious, severe, and maximum ABSI categories, p=0.001 (p<0.05) and the BOBI 50% category as many as three people and 85% as many as one person, p=0.0001 (0<0.05). Length of stay based on the ABSI score for the length of stay was 23 days with an ABSI score of 12-13 (maximum), and based on the BOBI Score, the majority was 28 days with a BOBI score of 8 (85%). ABSI in this study had a sensitivity of 100% and a specificity of 86.4%, while the use of BOBI in this study had a sensitivity of 100% and a specificity of 88.1%. Discussion: The BOBI scoring system is more accurate than the ABSI. This difference may occur due to differences in demographics and quality of service in each region. Therefore, the analysis of the validity of the scoring model before the research is carried out in a new population is considered crucial to be carried out.